2017
DOI: 10.1038/nmat5024
|View full text |Cite
|
Sign up to set email alerts
|

Mechanotransduction-modulated fibrotic microniches reveal the contribution of angiogenesis in liver fibrosis

Abstract: The role of pathological angiogenesis on liver fibrogenesis is still unknown. Here, we developed fibrotic microniches (FμNs) that recapitulate the interaction of liver sinusoid endothelial cells (LSECs) and hepatic stellate cells (HSCs). We investigated how the mechanical properties of their substrates affect the formation of capillary-like structures and how they relate to the progression of angiogenesis during liver fibrosis. Differences in cell response in the FμNs were synonymous of the early and late stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
125
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(126 citation statements)
references
References 56 publications
0
125
0
1
Order By: Relevance
“…Primary LSECs almost pursued to lose their fenestrae out of normal environment regardless of the slight effect of curcumol in vitro. The process of hepatic angiogenesis is divided into many stages, and the effects of drug therapy on angiogenesis at different stages are also different . LSEC renewal differs in physiological and in pathological conditions .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary LSECs almost pursued to lose their fenestrae out of normal environment regardless of the slight effect of curcumol in vitro. The process of hepatic angiogenesis is divided into many stages, and the effects of drug therapy on angiogenesis at different stages are also different . LSEC renewal differs in physiological and in pathological conditions .…”
Section: Discussionmentioning
confidence: 99%
“…All these processes are regulated by the hypoxia‐inducible factor‐1α (HIF‐1α) . Basic and clinical research also showed that inhibition of LSEC angiogenesis and HSC paracrine effects could alleviate liver fibrosis …”
Section: Introductionmentioning
confidence: 99%
“…To prove this concept, the authors analyzed the mRNA profiles of LSECs at an early and a late stage of fibrosis. Indeed, mechanobiologically modulated LSECs in microfibrotic niches largely recapitulated the featured mRNA changes of LSECs during fibrosis progression in vivo . On a functional level, the authors observed that HSC activation was increased in early‐stage compared to late‐stage fibrosis.…”
mentioning
confidence: 85%
“…A recent publication in Nature Materials by Liu and colleagues investigated the role of mechanical tension generated during angiogenesis and its influence on the progression of liver fibrosis . For the purpose of this study, the authors developed a novel in vitro tool to study the interaction between liver sinusoidal endothelial cells (LSECs) and hepatic stellate cells (HSCs).…”
mentioning
confidence: 99%
See 1 more Smart Citation